Символы творчества - Komarowa, Nadeshda (проект байкал, 2006)
Spatial arts, including sculpture, exist in the material sphere of culture and model the spatial aspects of the universe by themselves… Dmitri Budazhabe’s sculpture appeared to link the epochs of the old oriental cultures to the modern life. His works are decorative objects and at the same time the rite symbols, which contain deep aspects of the Buddhism. The sculptures and vessels for incense bravely model the interior space and simultaneously play a leading part in it. They are maid artistically and first of all evoke peaceful feelings. The small steam of the incense smoke, coming out of special channels, continues to create the environment even beyond the vessel, involving the observer in the rite. The oriental images invite us to make philosophical conclusions and to search for eternal truth… Dmitri Budazhabe’s works are performed in bronze moulding. Together with exotic forms, each sculpture has particular meaning. Thus the names sound lyrical and romantic: «The Treasure that Fulfils Wishes», «Sarasvati (The Goddess of the Morning Star)», «The Warrior of Shambala» etc. Flexible sculptural bodies, plastic compositional decor and fleshy bulging forms recall melodies of the mysterious East and the eternal secret of the hidden symbols, that one’s curious mind aspires to reveal. Dmitri Budazhabe’s works are often designed for Buddhist temples, made by special request and used for rites. At the moment the author is finishing the work, which he considers to be of great moral importance: it is a 2 meter sculpture of Buddha for Dazan. When watching his work the sense of time disappears… There is no past; presence merges with future–only Aspiration for perfection moves the author’s hands.